Care model for Primary Care workers: Convergent Care Research - Roselma Lucchese; Camila Borges Ramos; Lauany Martins dos Santos Carneiro; Rodolfo Pereira de Brito; Ivânia Vera; Núbia Inocêncio de Paula; Graciele Cristina Silva; Henrique Senna Diniz Pinto; Eryelg Moura Tomé; Alexandre de Assis Bueno
ABSTRACT Objective: To verify the application of the Operative Group as a care tool for the workers of Primary Health Care, with a view to the constitution of mental health care at work. Method: Convergent Care Research as a research process and health workers as subjects. The intervention strategy as a proposal to accommodate the mental suffering of the worker was the Operative Group. Results: Two categories emerged: "Evidence of Suffering at Work" and "Group Learning: Group Reception by the Group". Final considerations: The use of the Operative Group has been assertive in providing the subjects with a space for listening to adversities in the work environment and active learning of reality, reflection and confrontation of basic fears, development of a pro-change project through peer and active learning of reality.